BIRD SYMBOLISM IN PERSIAN MYSTICISM POETRY - Marwoto, Irmawati (UI Scholars Hub, 2019)
This article discusses about bird symbolism in Persian Mysticism Poetry, because images of birds in Islamic mysticism are important symbols and are included in the prominent symbols among other symbols such as wine, roses and gardens. The bird symbol does not only have one single meaning, namely a symbol of the soul, but it also has another meaning. The bird symbol not only as a symbol of the soul but also as a symbol of certain people, experiences and creation. The Sufis who isolate themselves are symbolized as birds in the cage of exile, while Sufis who are killed are symbolized as holy birds that have returned to their nest. Those Sufis who meditate and concentrate are symbolized by birds of silence and the prophets, angels and saints are symbolized by birds flying in the heavenly garden. In, Indonesia, the study is important data which can give meaning to Islamic archeology, considering that Sufism, which was very influential in Indonesia, was spread by both the Persians and the Arabs. This research uses library data, which is collecting data about it, identifying, classifying and then analyzing it. From the results of the analysis it was found that the ideology of birds as a symbols of divinity, symbol s of a holy persons, free souls which materializes in the archaeological remains in the form of ornaments or decorations on ancient Islamic tombs such as the tombs of the Wali Sanga in Java and Madura. This is related to the depiction of birds as symbols of free spirits reaching heaven, the guardians and spreaders of Islam in Java and Madura.